2018
DOI: 10.1136/bmj.k341
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim use for urinary tract infection and risk of adverse outcomes in older patients: cohort study

Abstract: ObjectiveTo determine if trimethoprim use for urinary tract infection (UTI) is associated with an increased risk of acute kidney injury, hyperkalaemia, or sudden death in the general population.DesignCohort study.SettingUK electronic primary care records from practices contributing to the Clinical Practice Research Datalink linked to the Hospital Episode Statistics database.ParticipantsAdults aged 65 and over with a prescription for trimethoprim, amoxicillin, cefalexin, ciprofloxacin, or nitrofurantoin prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 26 publications
(51 reference statements)
1
54
0
Order By: Relevance
“…It may also be due to the possibility that nitrofurantoin efficacy was reduced in those with lower eGFRs but was offset by the high rates of trimethoprim resistance and thus resulted in apparent similar rates of reconsultation and re-prescription. Our finding that nitrofurantoin was associated with a reduced risk of death in those with moderate renal impairment is consistent with previously reported estimates in studies that compared nitrofurantoin with amoxicillin in the general population [ 18 , 19 ]. We also found a previously unreported lower risk of AKI associated with nitrofurantoin use across all three eGFR groups of our cohort.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It may also be due to the possibility that nitrofurantoin efficacy was reduced in those with lower eGFRs but was offset by the high rates of trimethoprim resistance and thus resulted in apparent similar rates of reconsultation and re-prescription. Our finding that nitrofurantoin was associated with a reduced risk of death in those with moderate renal impairment is consistent with previously reported estimates in studies that compared nitrofurantoin with amoxicillin in the general population [ 18 , 19 ]. We also found a previously unreported lower risk of AKI associated with nitrofurantoin use across all three eGFR groups of our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Trimethoprim (with or without sulfamethoxazole) prescribing is associated with an increased risk of hyperkalaemia, AKI, and death, compared to amoxicillin [ 16 19 ]. Amoxicillin accounts for only about 5% of prescribing for UTI in the UK [ 9 ] and thus is a less helpful comparator for clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular the development of AKI following the use of sulphonamides, nitrofurantoin and trimethoprim has been well described (9)(10)(11). A recent large British cohort study showed an increase of 72% and 48% in the odds of AKI following treatment with trimethoprim and ciprofloxacin respectively for UTI in older patients in the community (12). A large Canadian case control study also reported a two-fold increase of hospital acquired AKI during fluoroquinolone administration (17).…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobials, ranked in order of increasing MOR, included trimethoprim, co‐trimoxazole, norfloxacin, erythromycin, ciprofloxacin, roxithromycin, nitrofurantoin, and flucloxacillin. The finding that trimethoprim (MOR = 1.68; 95%CI = [1.54‐1.80]) poses the highest risk of AKI among the antimicrobial class is supported by evidence from another population‐level cohort study conducted in older adults using the UK primary care database, Clinical Practice Research Datalink . This UK study found that trimethoprim (adjusted OR 1.72, 95% CI [1.31‐2.24]) and ciprofloxacin (adjusted OR 1.48, 95% CI [1.03‐2.13]) increased the odds of AKI compared with amoxicillin.…”
Section: Discussionmentioning
confidence: 99%